All in the Game: Communitarianism and The Wire. (2nd January 2017) - Painter, Chad
Abstract : Communitarian ethicists argue that social identity is formed by community relationships, emphasizing the connection between an individual and his or her community. News organizations are part of that community. Indeed, journalism only functions properly in terms of the public and public life, and as part of a larger community. This textual analysis study focused on the breakdown of the fictional Baltimore community depicted in the television series The Wire . Five institutions—the police force and justice system, the labor force, local and state politicians and government, the educational system, and the daily newspaper—have failed, and, in turn, the city is failing. Through the lens of communitarian ethics, the researcher argues that community stakeholders must recognize the need for a strong community from which the press can operate to report, explain, correct, and connect.